2020
DOI: 10.15560/16.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Boeica multinervia K.Y. Pan (Gesneriaceae): a new record for India

Abstract: We present the first record of Boeica multinervia (Gesneriaceae) for India, based on specimens from Sagalee, Arunachal Pradesh, India. The species is easily recognized due to its short internodes, stoloniferous habit, and glandular pubescent rosette leaves and inflorescence. Boeica multinervia is so far known only from (Xizang) China. A brief description along with additional notes and photographs are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Singh (Taram et al, 2021). While working on the floristic diversity of Eastern Himalayan state Arunachal Pradesh, India (Borah et al 2019, 2020a, 2020b, 2020c, 2020d, 2020e, 2020f; Taram et al 2020a, 2020b, 2020c, 2021), the authors encountered an interesting species of Henckelia . Detailed study of Henckelia species of India and adjoining countries, including protologues, type specimens, other herbarium specimens and relevant taxonomic literature (Clarke, 1874, 1884; Chatterjee, 1948; Don, 1825; Kanthraj et al, 2020; Krishna & Lakshminarasimhan, 2018; Sinha & Datta, 2016; Sirimongkol et al, 2020; Taram et al, 2020b, 2021; Wang et al, 1998; Wood, 1974; Yang et al, 2019) revealed it to be a Henckelia longipedicellata (B.L.Burtt) D.J.Middleton & Mich.Möller (Basionym: Chirita longipedicellata B.L.Burtt).…”
Section: Introductionmentioning
confidence: 99%
“…Singh (Taram et al, 2021). While working on the floristic diversity of Eastern Himalayan state Arunachal Pradesh, India (Borah et al 2019, 2020a, 2020b, 2020c, 2020d, 2020e, 2020f; Taram et al 2020a, 2020b, 2020c, 2021), the authors encountered an interesting species of Henckelia . Detailed study of Henckelia species of India and adjoining countries, including protologues, type specimens, other herbarium specimens and relevant taxonomic literature (Clarke, 1874, 1884; Chatterjee, 1948; Don, 1825; Kanthraj et al, 2020; Krishna & Lakshminarasimhan, 2018; Sinha & Datta, 2016; Sirimongkol et al, 2020; Taram et al, 2020b, 2021; Wang et al, 1998; Wood, 1974; Yang et al, 2019) revealed it to be a Henckelia longipedicellata (B.L.Burtt) D.J.Middleton & Mich.Möller (Basionym: Chirita longipedicellata B.L.Burtt).…”
Section: Introductionmentioning
confidence: 99%